Moringa Oleifera Root Extract for Sustainable Copper Oxide and Cobalt Oxide Nanoparticle Fabrication and Analysis Via Environmentally Friendly Synthesis - Pol, Umesh Nilkanth (International Journal of Membrane Science and Technology, 2023)
Presently, scientists commonly employ natural substances as reducing and stabilizing agents for the synthesis of copper oxide nanoparticles (CuO-NPs) and cobalt oxide nanoparticles (CoO NPs) due to their environmentally friendly, convenient, cost-effective, and feasible attributes. Using an eco-friendly approach, non-toxic and economical CuO nanoparticles were synthesized using moringa oleifera root extract. The optical properties of the copper oxide and cobalt oxide nanoparticles, synthesized via green methods, were elucidated using UV-visible spectroscopy. Fourier transform infrared spectroscopy (FTIR) was employed to investigate the active biomolecules and functional groups engaged in the biological reduction of metal ions into nano-scale CuO and CoO particles. X-ray diffraction analyses were conducted to scrutinize the structure, phase, and crystalline planes of the nanoparticles. The experimental results underscore that moringa oleifera root holds promise as a cost-effective and beneficial bio-resource for producing metal oxide nanoparticles. These standardized nanoparticles exhibit potential applications across various fields such as medicine, industry, and the environment. The study establishes the bioactivity and potential applications of environmentally friendly metal oxide nanoparticles.